Impact of soil microbial processes on the fate of crude oil contamination: Insights from aerobic and anaerobic microcosms - Rakiya Muhammad; Christopher Boothman; Hokyung Song; Jonathan R. Lloyd; Bart E. van Dongen (Applied Geochemistry, 2026)

Probing the mechanisms of Fe(III)/As(V) reduction and As mobilisation using mineral-coated sands; impact of electron donor treatments - Oliver C. Moore; Laura A. Richards; Christopher Boothman; Sam Shaw; Babajide Milton Macaulay; David A. Polya; Bart E. van Dongen; Jonathan R. Lloyd (Science of The Total Environment, 2025)

Control of cyanobacterial growth with potassium; implications for bloom control in nuclear storage ponds - Kejing Zhang; Lynn Foster; Christopher Boothman; Naji M. Bassil; Jon K. Pittman; Jonathan R. Lloyd (Harmful Algae, 2024)

Assessing the impacts of oil contamination on microbial communities in a Niger Delta soil - Rakiya Muhammad; Christopher Boothman; Hokyung Song; Jonathan R. Lloyd; Bart E. van Dongen (Science of The Total Environment, 2024)

Copper bioreduction and nanoparticle synthesis by an enrichment culture from a former copper mine - Richard L. Kimber; Gretta Elizondo; Klaudia Jedyka; Christopher Boothman; Rongsheng Cai; Heath Bagshaw; Sarah J. Haigh; Victoria S. Coker; Jonathan R. Lloyd (Environmental Microbiology, 2023)
Microorganisms can facilitate the reduction of Cu 2+ , altering its speciation and mobility in environmental systems and producing Cu‐based nanoparticles with useful catalytic properties. However, only a few model organisms have been studied in relation to Cu 2+ bioreduction and little work has been carried out on microbes from Cu‐contaminated environments. This study aimed to enrich for Cu‐resistant microbes from a Cu‐contaminated soil and explore their potential to facilitate Cu 2+ reduction and biomineralisation from solution. We show that an enrichment grown in a Cu‐amended medium, dominated by species closely related to Geothrix fermentans, Azospira restricta and Cellulomonas oligotrophica , can reduce Cu 2+ with subsequent precipitation of Cu nanoparticles. Characterisation of the nanoparticles with (scanning) transmission electron microscopy, energy‐dispersive x‐ray spectroscopy and electron energy loss spectroscopy supports the presence of both metallic Cu(0) and S‐rich Cu(I) nanoparticles. This study provides new insights into the diversity of microorganisms capable of facilitating copper reduction and highlights the potential for the formation of distinct nanoparticle phases resulting from bioreduction or biomineralisation reactions. The implications of these findings for the biogeochemical cycling of copper and the potential biotechnological synthesis of commercially useful copper nanoparticles are discussed.

Generation of Alkalinity by Stimulation of Microbial Iron Reduction in Acid Rock Drainage Systems: Impact of Natural Organic Matter Types - Martha E. Jimenez-Castaneda; Carolina Scarinci; Adam Burke; Christopher Boothman; David J. Vaughan; Jonathan R. Lloyd; Bart E. van Dongen (Water, Air, & Soil Pollution, 2020)
To determine the role of organic matter in the attenuation of acid rock drainage (ARD), microcosm-based experiments were performed using ARD stimulated with plants and manures. Initial mineralogical, organic geochemical and microbial analyses indicated a predominance of goethite, a substantial amount of organic carbon originating from local sources, and a bacterial community comparable with those detected in a range of ARD sites worldwide. After 100 days of incubation, changes in the mineralogical, organic and microbiological composition of the ARD demonstrated that the plant additions stimulate microbes with the potential to degrade this organic matter but do not necessarily cause substantial Fe(III) reduction. Conversely, the greatest observed stimulation of Fe(III) reduction, associated with an increase in pH to near-neutral values, was observed using manure additions. These results demonstrate that the use of the optimal natural carbon source is important and can promote the metabolism of microorganisms potentially fuelling a range of geomicrobial processes, including iron and sulfate reduction.

Arsenate detoxification in a Pseudomonad hypertolerant to arsenic - Prerna C. Patel; Florence Goulhen; Christopher Boothman; Andrew G. Gault; John M. Charnock; Kiran Kalia; Jonathan R. Lloyd (Archives of Microbiology, 2007)